2021
DOI: 10.15252/embr.202051954
|View full text |Cite
|
Sign up to set email alerts
|

Mfn2 localization in the ER is necessary for its bioenergetic function and neuritic development

Abstract: Mfn2 is a mitochondrial fusion protein with bioenergetic functions implicated in the pathophysiology of neuronal and metabolic disorders. Understanding the bioenergetic mechanism of Mfn2 may aid in designing therapeutic approaches for these disorders. Here we show using endoplasmic reticulum (ER) or mitochondria‐targeted Mfn2 that Mfn2 stimulation of the mitochondrial metabolism requires its localization in the ER, which is independent of its fusion function. ER‐located Mfn2 interacts with mitochondrial Mfn1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 108 publications
(182 reference statements)
2
26
0
Order By: Relevance
“…MFN1/MFN2 are GTPase-mediated motility proteins that are abundantly found in mammals ( Song et al., 2009 ). Both these proteins include four major domains: the conserved GTPase catalytic binding domain at the N-terminus, the structural domains of the heptad repeat 1 (HR1) and heptad repeat 2 (HR2), and the C-terminal transmembrane structure domain ( Figure 1 ) ( Casellas-Diaz et al., 2021 ). MFNl/2 are capable of forming dimers by connecting hydrophobic heptapeptide repeat structural domains and facilitate outer mitochondrial membrane cohesion through GTPase hydrolysis, in which the fusion mitochondria share adenylate kinases, metabolites, and proteins ( Meeusen et al., 2006 ; Song et al., 2009 ; Qi et al., 2016 ; Cao et al., 2017 ; Casellas-Diaz et al., 2021 ).…”
Section: Mitochondrial Fusion and Fission Dynamicsmentioning
confidence: 99%
“…MFN1/MFN2 are GTPase-mediated motility proteins that are abundantly found in mammals ( Song et al., 2009 ). Both these proteins include four major domains: the conserved GTPase catalytic binding domain at the N-terminus, the structural domains of the heptad repeat 1 (HR1) and heptad repeat 2 (HR2), and the C-terminal transmembrane structure domain ( Figure 1 ) ( Casellas-Diaz et al., 2021 ). MFNl/2 are capable of forming dimers by connecting hydrophobic heptapeptide repeat structural domains and facilitate outer mitochondrial membrane cohesion through GTPase hydrolysis, in which the fusion mitochondria share adenylate kinases, metabolites, and proteins ( Meeusen et al., 2006 ; Song et al., 2009 ; Qi et al., 2016 ; Cao et al., 2017 ; Casellas-Diaz et al., 2021 ).…”
Section: Mitochondrial Fusion and Fission Dynamicsmentioning
confidence: 99%
“…A study identified that the RBP TTP could inhibit NLRP3 expression in human macrophages by targeting the AU-rich elements in the NLRP3 3′- UTR [ 146 ], which might influence the development of diabetes. Mitofusin-2 (Mfn2) play a critical role in diabetes through promoting glucose oxidation, insulin sensitivity, mitochondria and endoplasmic reticulum function [ [147] , [148] , [149] , [150] ]. A study identified that RBP HuD increased Mfn2 expression by binding to 3′UTR of Mfn2 mRNA [ 138 ].…”
Section: Rna-rbps Interaction In Diabetes and Its Complicationsmentioning
confidence: 99%
“…MFN2 in the ER membrane can form either homotypic or heterotypic contacts with either MFN1 or MFN2 in the OMM ( de Brito and Scorrano, 2008a ; Casellas-Díaz et al, 2021 ), and initial studies showed that MFN2 depletion leads to reduced numbers of MERCs ( de Brito and Scorrano, 2008b ). Moreover, functional studies showed that MFN2 is important for phospholipid transfer ( Area-Gomez et al, 2012 ) and Ca 2+ uptake ( de Brito and Scorrano, 2008b ), consistent with a role in mediating MERCs.…”
Section: Introductionmentioning
confidence: 99%